2011
DOI: 10.1111/j.1524-4741.2011.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Seeding Following Percutaneous Breast Biopsy: Documentation With Comprehensive Imaging and Clinical Implications

Abstract: The aim of this study was to demonstrate convincing evidence that percutaneous breast biopsy may result in displacement of malignant cells that can initiate tumor growth at a separate anatomic site, other than the index lesion. Two patients with malignancy diagnosed by percutaneous breast biopsy were followed up with subsequent imaging. The observation of displaced cells initiating subsequent malignant growth was compared retrospectively with the previous year's outcomes following percutaneous breast biopsy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, prompt diagnosis and immediate pharmacological therapy may prevent such an occurrence. Needle-track tumor seeding after fine needle aspiration biopsy/core needle biopsy is another possible complication as with any other type of needle biopsy, although literature reports are controversial (Diaz et al, 1991;Nyland et al, 2002;Vignoli et al, 2007;Brenner and Gordon, 2011;Klopfleisch et al, 2011). In this small group of patients, we did not see any evidence of tumor spread or recurrence at the site of biopsy.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 61%
“…However, prompt diagnosis and immediate pharmacological therapy may prevent such an occurrence. Needle-track tumor seeding after fine needle aspiration biopsy/core needle biopsy is another possible complication as with any other type of needle biopsy, although literature reports are controversial (Diaz et al, 1991;Nyland et al, 2002;Vignoli et al, 2007;Brenner and Gordon, 2011;Klopfleisch et al, 2011). In this small group of patients, we did not see any evidence of tumor spread or recurrence at the site of biopsy.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 61%
“…It has previously been reported that inflammation can influence breast cancer recurrence , and that seeding through circulating cancer cells likely plays an integral role in the recurrence and metastasis of breast cancer . Recurrence of breast cancer at core needle biopsy skin sites has been previously described , and physiologic seeding of malignant cells may have happened at the time of initial mastectomy and tissue expander placement via a similar mechanism. One study reported perioperative washings of mastectomy sites as cytologically positive for malignant cells in 4% of patients, with risk factors being cutting of the tumor during removal, presence of positive margins, and presence of an extensive intraductal component to the tumor such as was present in this patient .…”
Section: Discussionmentioning
confidence: 99%
“…Another problem was that some investigators were concerned that incisional biopsies might increase the risk of cancer cell seeding and dissemination [20, 21]. Pisters et al found that a positive surgical margin was an independent adverse prognostic factor for local recurrence and survival in soft tissue sarcomas [22].…”
Section: Discussionmentioning
confidence: 99%